GAMBARAN KELUHAN MUSKULOSKLETAL PADA PENGRAJIN SASIRANGAN DI KAMPUNG SASIRANGAN SUNGAI JINGAH KEC. BANJARMASIN UTARA: GAMBARAN KELUHAN MUSKULOSKLETAL PADA PENGRAJIN SASIRANGAN DI KAMPUNG SASIRANGAN SUNGAI JINGAH KEC. BANJARMASIN UTARA - Enny Fauziah; Khusnul Safitri; Dian Intan Permatasari (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2023)
Work craft sasirangan especially those related to human strength and endurancein carrying out their work can cause problems that have so far been ignored, includingback pain, neck pain, wrist pain, which are called musculoskeletal disorders. So thatmusculoskeletal disorders be one reason happening accident work. Objective Thisresearch is to find out musculoskeletal disorders in sasirangan craftsmen. Thisresearch was conducted in Sasirangan Sungai Jingah Village, Kec. North Banjarmasinwith the method descriptively using the Nordic Body Map questionnaire measuring tool.The results showed that the average age of the sasirangan craftsmen was 35 years,based on the gender distribution, the most experienced musculoskeletal disorders werewomen with a percentage of 56.8%, based on the distribution of the average workingperiod of 5 years, based on the distribution of average working duration. 7 hours/daywith a percentage of 45.9%, based on the distribution of the average working positionsitting on the floor with a percentage of 54.0%, and based on the distribution ofrespondents who experience musculoskeletal disoders an average of 49.3 with aninterpretation of mild complaints, usually complain of pain in the lumbar area.